Triboelectric sensor array for internet of things based smart traffic monitoring and management system. (February 2022) - Yang, Xiya; Liu, Guangqing; Guo, Qiyao; Wen, Haiyang; Huang, Ruiyuan; Meng, Xianghe; Duan, Jialong; Tang, Qunwei
Abstract: With the advanced technologies such as 5 G network and internet of things (IoT), there are incredibly increasing sensors and corresponding applications emerging to benefit our daily lives. However, the power supplies for countless sensors become a serious issue to suppress further expansion of IoT. In this work, a self-powered triboelectric sensor (CN-STS) made of electrospun composite nanofibers is developed towards smart traffic monitoring and management. To meet the requirements of fast-response and high sensitivity for the smart traffic management, transferred charge density is adopted as sensing signals compared to voltage / current outputs for it can perfectly record the subtle differences and suitable for dynamic traffic monitoring. Carbon nanotube is further doped into PVDF nanofibers to improve the electrical output performance and pressure sensitivity. A relatively high sensitivity of 0.0406 μ Cm −2 kPa −1 at low pressure range (0–75 kPa) and a sensitivity of 0.0032 μ Cm −2 kPa −1 at higher pressure range (75–425 kPa) can be achieved by the CN-STS, indicating that the CN-STS is more sensitive at low pressure range. Moreover, by connecting to cloud IoT services, the functions of traffic flow management, overlapping and speeding vehicle capturing, and plate number recognition are realized by the CN-STS arrays with a compensation circuit. A charge amplifier is utilized in power management to process the charge input signals for better distinguishing the signals from none-vehicles and stabilize the volage output for further reading by the A/D convertor build in Raspberry Pi. The engineered self-powered triboelectric sensors not only open a new potential area for triboelectric nanogenerators but also significantly popularize the IoT industry. Graphical Abstract: Triboelectric Sensor Array for Internet of Things based Smart Traffic Monitoring and Management System ga1 Highlights: Transferred charge density is adopted as sensing signals to meet the fast-response and high sensitivity of traffic management system. MWCNT is doped into electrospun PVDF nanofibers to enhance the electrical output performance and pressure sensitivity. Two segment regions of sensitivity are obtained with sensitivity of 0.0406 μ Cm −2 kPa −1 at low pressure range. Functions of speeding capture, overlapping, and plate number recognition are realized using a compensation circuit. Output voltage is stabilized to 3.3V using a charge amplifier for further reading by A/D convertor build in Raspberry Pi..